Vivero Centroamericano de Adaptacion y Rendimiento, VICAR 1981 y 1982 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1984)
In the 2nd semester of 1981 and in 1982, VICAR (Central American bean yield and adaptation nursery) carried out field tests with red and black- grain materials, with the participation of national programs from Honduras, El Salvador, Nicaragua, Costa Rica, and Guatemala. Data from the results obtained in these evaluations are included. Fourteen black and 14 red bean cv. from VICAR were used to evaluate their physical, chemical, technologic, and nutritional characteristics as well as the effect of the environment on the same parameters in several localities of Nicaragua, Honduras, El Salvador, Costa Rica, and Guatemala. Red and black beans exhibited different behaviors in some parameters. The wt. of red bean seeds seems to be the most appropriate parameter to improve yield and cooking time. The environment is highly influential on the chemical and physical characteristics of the var. studied. (CIAT)